Prodromus of a fern flora for Bolivia. VI. Psilotaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2017)
We provide a synopsis to the family Psilotaceae in Bolivia, consisting of the single species Psilotum nudum.